Upper Gastrointestinal Bleeding from Metastatic Testicular Embryonal Carcinoma - Jaudah A. Al Maghrabi,; Jamal M. Zekri, (Journal of King Abdulaziz University: Medical Sciences, 2023)
In contrast to primary duodenal adenocarcinomas, germ cell tumors are potentially curable even when metastatic. It is therefore important for clinician and pathologist to be aware of this entity for management decision. A rare case of metastatic embryonal carcinoma, which initially was presented as upper gastrointestinal tract bleeding is reported. The patient was treated with 4 cycles of bleomycin, etoposide, and cisplatin and revealed a good response. In young men with a malignant tumor in the upper gastrointestinal tract, the diagnosis of germ cell tumors should be considered even in the absence of a palpable testicular mass.